Perspectives on the Pandemic: Contemporary Personal Essays as a Space of Resistance (Altre Modernità, 2022)
It may be argued that writing about contemporaneity risks being a mere description of what Braudel would term ‘episodic time’—the short-term perspective of newspapers and chronicles. However, when political and social events spread into literature, there is a nuanced language of presence (Barthes). By not being bound to a specific mode of narration, the essay’s brevity and incisiveness seems particularly suitable to decipher the contemporary. This paper presents a comparative reading of personal essays published between April and July 2020 by Olive Senior, Deborah Levy, and Zadie Smith, and it argues that there are two main ways of resisting: the choice of writing in itself, and the choice of topics and issues. The immediate response of writers in the form of essays published in book form, in online magazines, or special sections of the websites of publishing houses is a clear example of how literature—and indeed the literary mind—can be a space for thinking about the present and putting things into perspective. By overcoming the possible limitations represented by the thematization of the pandemic, the writers open towards what may appear as a different, but still very close, temporality: that of physical and discourse-based violence on female bodies, on black bodies, and on the Earth. This paper will then come to the conclusion that writing is an act of resistance and that literature has the power to narrate the real “interpret[ing] the world […] one word at a time” (Senior, “Cross Words”).
Keywords: personal essay; contemporaneity; pandemic; writing as an act of resistance